'It Helped Me Sort of Face the End of the World': The Role of Emotions for Third Sector Climate Change Engagement Initiatives. (1st October 2015) - Büchs, Milena; Hinton, Emma; Smith, Graham
Abstract : This paper examines the role that attention to emotions around climate change can play for third sector climate change engagement initiatives, an area to which the literature on such initiatives has paid little attention. It focuses on Carbon Conversations, a programme that explicitly acknowledges the role of difficult emotions and underlying values in people's engagement with climate change. While there are limitations to this approach, results show that it can help certain audiences engage more deeply with issues around climate change and carbon reduction. Important lessons can be drawn for other initiatives that aim to engage the public on climate change.